Internalization of Islamic Education Values Through Program Takhaṣṣuṣ Qirāʾatul Kutub - Tasya, Defina; Mahariah, Mahariah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This research aims to analyze the process of internalizing Islamic education values through the program Takhaṣṣuṣ Qirāʾatul Kutub, including program implementation, educator strategies, impact on students, supporting and inhibiting factors. This research uses qualitative research methods with a case study approach to the program Takhaṣṣuṣ Qirāʾatul Kutub in Ma’had Zainul Umam located on Jalan Lapangan Pasar 15 Dusun VI Bandar Setia, Kecamatan Percut Sei Tuan, Kabupaten Deli Serdang, Province of North Sumatra. Data collection techniques through observation, interviews, and documentation study. After that, data analysis is conducted through reduction, presentation, and conclusion drawing. Ensuring data validity using triangulation techniques. The research results show that the implementation of the program Takhaṣṣuṣ Qirāʾatul Kutub is structured from the daily activities of the students to the yellow book-based teaching schedule, which includes the internalization of Islamic education values through strategies of exemplary behavior, habituation, advice, discipline, supervision, and intensive attention. The process of value internalization is carried out in three stages: transformation, transaction, and trans-internalization of values, thereby having a lasting impact on the students, covering aspects of faith, worship, and morals. The supporting factors are the consistent implementation of the program, quality educators, a conducive learning environment, a structured and systematic learning system, support from parents and the community, and the strong determination of each student to become a better individual. The inhibiting factors are the external environment and negative peers, the limited duration of the program, and the student's inability to fully control themselves well.